PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP 3 PARIAMAN - Viola Gusmarlina (Departemen Matematika, 2022)
The purpose of this study was to determine whether student learning outcomes using the Student Teams Achievement Division type cooperative learning model are better than students using conventional learning in class VIII SMPN 3 Pariaman. This type of research is a quasi-experimental research with a static group design. The results of data analysis with = 0.05 obtained P-Value = 0.00 which means rejecting H0. Thus, it can be said that the learning outcomes of students who were taught using the cooperative learning model of the Student Team Achievement Division type are better than those taught by conventional learning in class VIII of SMPN 3 Pariaman.Keywords ― Cooperative Learning Model, Mathematics Learning Outcomes, Student Teams Achievement Division